Implementation and application of a Monte Carlo model for an in vivo micro computed tomography system. (December 2017) - Manser, Peter; Peter, Silvia; Volken, Werner; Zulliger, Martin A.; Laib, Andres; Koller, Bruno; Fix, Michael K.
Highlights: Monte Carlo implementation of a micro-CT scanner (XtremeCT) Validation of MC model using measurements. Extensions of MC model to enable the analysis of scatter components. Scatter component analysis for different situations. Abstract: Micro computed tomography (µCT) scanners are used to create high-resolution images and to quantify properties of the scanned objects. While modern µCT scanners benefit from the cone beam geometry, they are compromised by scatter radiation. This work aims to develop a Monte Carlo (MC) model of a µCT scanner in order to characterize the scatter radiation in the detector plane. The EGS++ framework with the MC code EGSnrc was used to simulate the particle transport through the main components of the XtremeCT (SCANCO Medical AG, Switzerland). The developed MC model was based on specific information of the manufacturer and was validated against measurements. The primary and the scatter radiation were analyzed and by implementing a dedicated tracing method, the scatter radiation was subdivided into different scatter components. The comparisons of measured and simulated transmission values for different absorber and filter combinations result in a mean difference of 0.2% ± 1.4%, with a maximal local difference of 3.4%. The reconstructed image of the phantom based on measurements agrees well with the image reconstructed using the MC model. The local contribution of scattered radiation is up to 10% of the total radiation in the detector plane and most of the scattered particles result from interactions in the scanned object. The MC simulations show that scatter radiation contains information about the structure of the object. In conclusion, a MC model for a µCT scanner was successfully validated and applied to analyze the characteristics of the scatter radiation for a µCT scanner.